Estudo soroepidemiológico da infecção pelo vírus da imunodeficiência humana em mulheres profissionais do sexo em Goiânia-Goiás - CAETANO, Karlla Antonieta Amorim (2011)
A biological and behavioral surveillance survey was carried out employing the Respondent Driven Sampling methodology, between May 2009 and June 2010, to estimate the prevalence and risk factors/risk behaviors for HIV among female sex workers (FSW) in Goiânia city, Goiás, as well as their knowledge about this disease. The participants were interviewed and blood samples were taken and tested for antibodies against HIV-1 and HIV-2, and confirmed by Western blot. All women enrolled were counseled on HIV and safer sex practices. Behavioral survey and biological testing data were analyzed using RDSAT 5.6. Of the 395 women, most (67.1%) were single, half (56.9%) had between 21 and 30 years old, and 10 to 12 years of education (47.4%). Some women (14.3%) reported to recruit their clients in more than one type of venue, being nightclubs (41%), bars (27.7%) and streets (25%) predominant. Regarding the last day of work, 52.7% of women reported two or more clients. Daily income ranged from US$ 8,00 to US$ 833,00. Of the women, 87.1% reported regular condom use with clients in the last 30 days. However, condom use with non-paying partners in last one year was reported by 20.9% of women. Regarding the thirty days prior to interview, 85.2% of FSW reported having drunk alcohol and 34.1% reported having used illicit drugs. Only 26.7% of FSW obtained condom in health services. Vaginal discharge and genital ulcer in last year was reported by 49% and 8.6% of FSW, respectively. Of the total, 37.4% of FSW mentioned midge bites as a form of viral transmission, and 17.4% sharing utensils with infected persons. Virtually all women (99%) acknowledged the transmission of the virus by sharing needles contaminated. Also, 90.6% of FSW are aware that pregnant women can transmit the HIV to their babies, but almost half (45.5%), unaware of the measures to prevent vertical transmission of HIV in the pregnancy. It was estimated that 1.8% of women were HIV positive. In addition, most anti-HIV positive (5/6) was found in women working in the streets. The findings of this study suggest the risk for HIV infection among FSW in Goiânia, highlighting the need of health promotion and prevention for this population, mainly among those who recruit their clients in the streets.